PERAN MEDIA DALAM MENGATASI KESULITAN BELAJAR DAN RENDAHNYA MOTIVASI BELAJAR MURID DI SEKOLAH DASAR - Habibah, Siti; Fita Ama, Sentia; Efendi Hutagalung, Erwin; Muhammadin Al Fath, Ayatullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the role of learning media in addressing learning difficulties and improving students’ motivation in elementary schools. The problem identified is that many students experience difficulties in understanding learning materials, low motivation, and limited active participation due to the lack of varied teaching methods and ineffective use of instructional media. The purpose of this study is to analyze how learning media can overcome these issues and enhance the quality of the learning process. This research employs a literature review approach using a traditional review method by collecting and analyzing relevant national journal articles published within the last five years. Data were gathered through academic databases and analyzed using content analysis techniques, including data reduction, data presentation, and conclusion drawing. The findings indicate that learning media play a significant role in making abstract concepts more concrete, increasing students’ engagement, and improving their understanding of learning materials. Furthermore, the use of interactive, visual, and game-based media can enhance students’ motivation, participation, and critical thinking skills. However, challenges such as limited facilities and teachers’ competencies in utilizing media effectively still exist. Overall, the study concludes that the appropriate and creative use of learning media contributes significantly to improving the effectiveness, efficiency, and meaningfulness of the learning process in elementary education.